CLOUD DATA GOVERNANCE SECURITY CHECKLIST AT INFRASTRUCTURE AS A SERVICE FOR HIGH-PERFORMANCE COMPUTING DATA CENTER - ABU SAED, KAMARIAH (2020)
High-Performance Cloud Computing Data Center offers great advantages in terms of flexibility and cost saving. However, this advancement also comes with drawbacks that can lead to business failure. One issue that becomes a concern when implementing the cloud computing is data management and security within the cloud. This study investigates the implementation of data governance in cloud services focusing on IaaS. The scope of this study is for high-performance computing (HPC) data center that provides IaaS cloud service for their users. This study will investigate threats that affect IaaS and how HPC data center mitigates the issues.